Antidiabetic and Antidiarrheal Activity from Extract of Namnam (Cynometra Cauliflora) Leaf - Sumarlin, La Ode; Suprayogi, Agik; Rahminiwati, Min; Satyaningtijas, Aryani; Sukandar, Dede; Nugraha, Ahmad Tjahja; Amalia, Ika (Proceeding International Conference on Global Resource Conservation, 2015)
In addition to decorate the yard, plant namnam (Cynometra cauliflora) turns out to have merit as an herbal remedy because it has biological activities such as antimicrobial, antioxidant, cytotoxic, antiviral, anti-inflammatory, antitumor and antidiabetic. It is study will add to scientific information about plants Namnam the potential to be developed as a functional food and natural herbal remedies in particular as antidiabetic agents and antidiarrheal. Ability as an antidiabetic agent tested by the ability of plants Namnam inhibit Î±-amylase. Meanwhile, antidiarrheal activity will be tested against the isolated rabbit intestine recorded on kymograph. The analysis showed that the leaf extract of plant Namnam (C. cauliflora) at a concentration of 100 mg/mL, 250 mg/mL and 300 mg/mL each is able to inhibit Î±-amylase activity by 20.68%; 70.24% and 72.59% and IC50 of 200.67 Â± 0.53 mg/mL. The study also showed that the sample tested has the ability to decrease the activity of isolated rabbit intestine in the pattern described in kymograph. Thus the plant leaves Namnam (C. cauliflora) potential to be developed as antidibetes agent and antidiarrheal.Â This may partially explain the use in traditional medicine for the treatment of diarrhea. These results support their use in folk medicine.Keywords: Antidiabetic, antidiarrheal, Â Cynometra cauliflora, Namnam